An unusual case of spinal manifestations of sickle cell disease (Indian Journal of Case Reports, 2017)
Sickle cell disease (SCD) results from the presence of abnormal beta globin chains within hemoglobin. Overtime, the disease produces various spinal abnormalities as a result of chronic anemia which include marrow hyperplasia, reversion of yellow marrow to red marrow, and occasionally extramedullary hematopoiesis. Vaso-occlusion may manifest as ischemia and infarction whereas superimposed infection may lead to osteomyelitis. There is paucity of literature illustrating the spinal manifestations of the SCD in a single case. Hence, in the present work, we report the case of a 30-year-old male with SCD who presented with almost all the manifestations of the disease in the spine.